Upaya Guru PAI dalam Peningkatan Hasil Belajar Materi Thaharah Siswa Kelas IV di SD Mathla'ul Khoeriyah Bandung - Fauziah Dewi Rahayu; Nan Rahminawati; Ikin Asikin (Bandung Conference Series: Islamic Education, 2023)
Abstract. In PAI learning the lowest learning achievement was in Thaharah material, this shows that 33 grade IV students at SD Mathlaul Khoeriyah Bandung achieved a KKM score of only 60%, while 40% of students did not achieve a KKM score. The research method used in this study is a qualitative approach, descriptive method and case studies. Data collection techniques through interviews, observation and documentation. Data analysis techniques: data reduction, data presentation, and verification/conclusion. 1) The existing condition of Islamic education learning in grade IV at SD Mathla'ul Khoeriyah Bandung, teachers still use conventional methods in class, namely passive students and less conducive learning, resulting in low student learning outcomes. The material with the lowest KKM score is in Thaharah material 2) PAI teacher's efforts in improving learning outcomes of class IV thaharah material which has low KKM scores in SD Mathla'ul Khoeriyah Bandung, namely teacher's efforts through the process of implementing learning, teacher's efforts through school programs, teacher giving reward and punishment efforts through increasing student motivation, the teacher is able to understand the character of the students, the teacher establishes good communication with parents of students, the teacher attends teacher training workshops. 3) The results of learning thaharah material for grade IV students at SD Mathla'ul Khoeriyah after the efforts made by PAI teachers in improving student learning outcomes in thaharah material. written test, oral test, and practice. During the learning process, students are active, communicative, disciplined, and pay attention to the teacher. Abstrak. Pada pembelajaran PAI pencapaian hasil belajar yang paling rendah adalah pada materi Thaharah, hal ini menunjukkan bahwa 33 siswa kelas IV di SD Mathlaul Khoeriyah Bandung mencapai nilai KKM hanya 60%, sedangkan 40% siswa tidak mencapai nilai KKM. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif, metode deskriptif dan studi kasus. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Teknik analisis data : reduksi data, penyajian data, dan veruvikasi/penarikan kesimpulan. 1) Kondisi eksisting pembelajaran PAI kelas IV di SD Mathla’ul Khoeriyah Bandung guru masih menggunakan metode konvensional di kelas, yaitu siswa pasif dan pembelajaran kurang kondusif, mengakibatkan hasil belajar siswa tetap rendah. Materi dengan nilai KKM terendah yaitu pada materi Thaharah 2) upaya guru PAI dalam peningkatan hasil belajar materi thaharah kelas IV yang memiliki nilai KKM rendah di SD Mathla’ul Khoeriyah Bandung yaitu Upaya guru melalui proses pelaksanaan pembelajaran, Upaya guru melalui program sekolah, Guru memberikan reward dan punishment upaya melalui peningkatan motivasi siswa, Guru mampu memahami karakter siswa, Guru menjalin komunikasi baik dengan orang tua siswa, Guru mengikuti workshop pelatihan guru. 3) Hasil belajar materi thaharah siswa kelas IV di SD Mathla’ul Khoeriyah setelah upaya yang dilakukan guru PAI dalam peningkatan hasil belajar ketuntasan siswa pada materi thaharah jumlah keseluruhan siswa kelas IV 33 orang lulus standar mutu mata pelajaran PAI dari KKM 80 nilai yang didapatkan berdasarkan tes tulis, tes lisan, dan praktek. Pada saat proses pembelajaran berlangsung siswa aktif, komunikatif, disiplin, dan memperhatikan guru.